A comprehensive review on clove (Caryophyllus aromaticus L.) essential oil and its significance in the formulation of edible coatings for potential food applications - Kumar Pandey, Vinay; Shams, Rafeeya; Singh, Rahul; Dar, Aamir Hussain; Pandiselvam, R.; Rusu, Alexandru Vasile; Trif, Monica (Frontiers in Nutrition, 2022)
Many studies have demonstrated the use of synthetic preservatives and chemical additives in food is causing poisoning, cancer, and other degenerative disorders. New solutions for food preservation with quality maintenance are currently emerging. As a result, public concern has grown, as they desire to eat healthier products that use natural preservatives and compounds rather than synthetic ones. Clove is a highly prized spice used as a food preservative and for a variety of therapeutic reasons. Clove essential oil and its principal active component, eugenol, indicate antibacterial and antifungal action, aromaticity, and safety as promising and valuable antiseptics in the food sector. Clove essential oil and eugenol are found to have strong inhibition effects on a variety of food-source bacteria, and the mechanisms are linked to lowering migration and adhesion, as well as blocking the creation of biofilm and various virulence factors. This review emphasizes the importance of CEO (clove essential oil) in the food industry and how it can be explored with edible coatings to deliver its functional properties in food preservation.